2023
DOI: 10.1101/2023.01.05.23284205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal and meteorological trends in dengue transmission in the Dominican Republic, 2015-2019

Abstract: Dengue has broadened its global distribution substantially in the past two decades, and many endemic areas are experiencing increases in incidence. The Dominican Republic recently experienced its two largest outbreaks to date with 16,836 reported cases in 2015 and 20,123 reported cases in 2019. With this upward trend in dengue transmission, developing tools to better prepare healthcare systems and mosquito control agencies is of critical importance. Before such tools can be developed, however, we must first be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Additionally, variations in average temperature (Temp.avg) have the greatest effect on dengue cases. These results are in agreement with similar studies that found significant risk of dengue when considering lags in climate variables of 2-5 weeks [3,4]. Our findings provide a better understanding of the relationships between meteorological conditions and weekly trends in dengue cases during the outbreak that occurred in the Dominican Republic in 2019.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, variations in average temperature (Temp.avg) have the greatest effect on dengue cases. These results are in agreement with similar studies that found significant risk of dengue when considering lags in climate variables of 2-5 weeks [3,4]. Our findings provide a better understanding of the relationships between meteorological conditions and weekly trends in dengue cases during the outbreak that occurred in the Dominican Republic in 2019.…”
Section: Discussionsupporting
confidence: 92%
“…One country where dengue has long been endemic is the Dominican Republic. In the past decade, however, dengue outbreaks have grown in incidence, with the 2019 outbreak being the largest outbreak in the country to date [3,4]. In fact, 2019 was the year in which the WHO recorded the highest number of global dengue cases ever to occur within a year [1], suggesting that dengue in the Dominican Republic is mirroring global trends.…”
Section: Introductionmentioning
confidence: 99%
“…2 In comparison, there were ≈1300–1500 dengue cases in the prior 2 years in the Dominican Republic. 7…”
mentioning
confidence: 99%